2003
DOI: 10.1046/j.1542-474x.2003.08202.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of P‐wave Dispersion on Atrial Fibrillation in Patients with Acute Anterior Wall Myocardial Infarction

Abstract: Although P maximum and P dispersion are significant predictive factors of AF in patients with acute anterior wall MI in the univariate analysis, on the basis of multivariate analysis, only age and LVEF were independent predictive parameters for AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 49 publications
6
28
0
1
Order By: Relevance
“…5 The study conducted by Baykan, et al showed that P wave dispersion was significantly higher in patients with AF than in patients without AF (P = 0.01). 12 Similar other study showed that P dispersion increased significantly during spontaneous angina (P < 0.001). 10 P wave dispersion was significantly higher in 60 patients with paroxysmal lone AF than in 40 healthy controls (p <0.0001) in another study.…”
Section: Discussionsupporting
confidence: 61%
“…5 The study conducted by Baykan, et al showed that P wave dispersion was significantly higher in patients with AF than in patients without AF (P = 0.01). 12 Similar other study showed that P dispersion increased significantly during spontaneous angina (P < 0.001). 10 P wave dispersion was significantly higher in 60 patients with paroxysmal lone AF than in 40 healthy controls (p <0.0001) in another study.…”
Section: Discussionsupporting
confidence: 61%
“…PD is a noninvasive indicator of intra-atrial conduction heterogeneity producing substrate for reentry, which is a pathophysiological mechanism of atrial fibrillation [16,17]. PD has been studied in some other conditions such as hypertension [18], obesity [19], diabetes mellitus [20], metabolic syndrome [21], dilated cardiomyopathy [22], myocardial infarction [23], atrial septal defect [24], hypertrophic cardiomyopathy [25], obstructive sleep apnea [26] and Wilson's disease [27]. The exact mechanism of PD prolongation in these clinical conditions is not well known, but it is thought that structural and electrophysiological changes in the atrial myocardium caused by elevated plasma volume [28], ventricular diastolic dysfunction [29] and enhanced neurohormonal activation [30], that accompany these diseases, may contribute to left atrial enlargement and electrical instability.…”
Section: Discussionmentioning
confidence: 99%
“…It is shown that P wave durations and P wave dispersion on electrocardiogram both measured in a very early period of acute 0167-5273/$ -see front matter D 2004 Elsevier Ireland Ltd. All rights reserved. doi:10.1016/j.ijcard.2004.04.004 myocardial infarction are useful in predicting atrial fibrillation [12,13]. It is also shown that both advanced left ventricular systolic and diastolic dysfunctions are frequently associated with the occurrence of atrial fibrillation following acute myocardial infarction [8,13,14].…”
Section: Introductionmentioning
confidence: 99%